Optimal Traffic Planning for Efficient Evacuation - Khadka, S. R. (Journal of Advanced College of Engineering and Management, 2016)
Efficient traffic planning during evacuation in emergency has been important issue. The planning based on research significantly improves the quality of the emergency management. In this paper, we discuss on both optimization and simulation approaches of the traffic planning. Both approaches have been extensively studied in the literature with efficient softwares. Journal of Advanced College of Engineering and Management, Vol. 1, 2015, pp. 119-126